(untitled) (Research, Society and Development, 2021)
The objective of this research was to evaluate the generation of fish waste and the environmental perception of fishmongers regarding the environmental impacts caused by temporary storage and final disposal of waste generated in three open markets in the city of Marabá - Pará. The method used was inductive with quantitative and qualitative comprehensiveness. Four in loco visits were made to obtain primary data. The secondary data were obtained from free access electronic links. The analysis of data obtained indicated that nine kinds of fish are commercialized; the largest quantity occurred at the fair of 28 (2. 114.9 kg/month); three types of organic waste were identified and quantified: one (skins: 77.4±0.0); two (carcass, 14.0±4.7) and three (others 88.4±21.6); temporary storage is done in buckets (8.3±1.5) and 100 L plastic bags (2.3±1.5), it was observed that there is no residual segregation (6.7±3.1); all sampled individuals (n = 36: 100%) reported that the waste collected by the municipality, is destined to the controlled landfill without proper treatment. Regarding the environmental perception of impacts caused by improper disposal, there is still ignorance about it (7.0±2.0); the vast majority of them have no knowledge about the sustainable alternatives for organic waste (7.3±0.6), but the minority knows (3.7±2.9), and they cited animal feed (5.0±2.7) and organic manure (2.0±3.1) as appropriate solutions. Therefore, the hygienic and sanitary conditions in the three markets are not adequate and urgently need corrections to adapt to the sanitary and environmental laws, such as Resolution CONAMA 275/01.